Penerapan ai pada NPC dalam game “zombie attack” dengan metode FSM - Yogie Wilvren Saragih; Samuel Krispama Lumbantoruan; Wahyu S.J. Saputra (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
Games are one of the entertainment media that are in great demand by the public. The development of the game genre is so rapid, causing the game to attract more people. Each type of game has its own advantages and disadvantages. Artificial intelligence is needed to determine what behavior is carried out under certain conditions. The Zombie Attack game that was built is a type of game, namely Shooter, involving various patterns of artificial intelligence implanted in non-player characters (NPCs).